The association of polyunsaturated fatty acids and asthma: a cross-sectional study - Gangtie Liu; Hengbo Ye; Qian Cheng; Jian Zhao; Congcong Ma; Huichao Jie (BMC, 2023)
Abstract Background To examine the relationships between polyunsaturated fatty acids (PUFAs) dietary intake and asthma in children. Methods In this cross-sectional study, a total of 14,727 participants from the United States National Health and Nutrition Examination Survey (NHANES) database in 1999-2018 were included, and the baseline characteristics of all participants were gathered. The description analysis was used to explore the possible covariates. Weighted multivariate logistic regression models were adopted to assessed the association between PUFAs dietary intake and asthma in children. In addition, we also performed subgroup analysis based on gender, age, and maternal smoking during pregnancy to investigate this relationship. Results The prevalence of asthma approximately was 15.38% in the present study. The result of weighted multivariate logistic regression indicated that, docosahexaenoic [weighted odds ratio (OR) = 0.37, 95% confidence interval (CI) 0.19-0.74], total n − 3 PUFAs (weighted OR = 0.63, 95%CI 0.43-0.91), and eicosapentaenoic (weighted OR = 0.35, 95%CI 0.13-0.95) dietary intake were negatively associated with asthma in children. The subgroup analysis described that when children were male (weighted OR = 0.28, 95%CI 0.10-0.84), or were 5-7 years (weighted OR = 0.04, 95%CI 0.01-0.37), were 7-12 years (weighted OR = 0.46, 95%CI 0.24-0.90), or their maternal smoking during pregnancy (weighted OR = 0.16, 95%CI 0.03-0.90), docosahexaenoic dietary intake was negatively related to childhood asthma. Conclusion Docosahexaenoic dietary intake was negatively associated with the asthma in children, especially if children were male, or were 5-12 years, or their maternal smoking during pregnancy.